Attenuated Salmonella enterica Serovar Typhimurium, Strain NC983, Is Immunogenic, and Protective against Virulent Typhimurium Challenges in Mice - Bryan Troxell; Mary Mendoza; Rizwana Ali; Matthew Koci; Hosni Hassan (Vaccines, 2020)
Non-typhoidal Salmonella (NTS) serovars are significant health burden worldwide. Although much effort has been devoted to developing typhoid-based vaccines for humans, currently there is no NTS vaccine available. Presented here is the efficacy of a live attenuated serovar Typhimurium strain (NC983). Oral delivery of strain NC983 was capable of fully protecting C57BL/6 and BALB/c mice against challenge with virulent Typhimurium. Strain NC983 was found to elicit an anti-Typhimurium IgG response following administration of vaccine and boosting doses. Furthermore, in competition experiments with virulent S. Typhimurium (ATCC 14028), NC983 was highly defective in colonization of the murine liver and spleen. Collectively, these results indicate that strain NC983 is a potential live attenuated vaccine strain that warrants further development.